Phage-resistance linked to cell heterogeneity in the commercial strain Lactobacillus delbrueckii subsp. lactis Ab1 - Suárez, Viviana Beatriz (2008)
The aim of this work was to study the relationship between the cell morphological heterogeneity and the phage-resistance in the commercial strain Lactobacillus delbrueckii subsp. lactis Ab1. Two morphological variants (named C and T) were isolated from this strain. Phage-resistant derivatives were isolated from them and the percentage of occurrence of confirmed phage-resistant cells was 0.001% of the total cellular population. Within these phage-resistant cell derivatives there were T (3 out of 4 total isolates) and C (1 out of 4 total isolates) variants. The study of some technological properties (e.g. proteolytic and acidifying activities) demonstrated that most of phage-resistant derivatives were not as good as the parental strain. However, for one derivative (a T variant), the technological properties were better than those of the parental strain. On the other hand, it was possible to determinate that the system of phage-resistance in the T variants was interference in adsorption step, with adsorption rates < 15%. For the C variant derivative it was possible to demonstrate the presence of a restriction/modification system and, moreover, to determinate that this system could be Type I R/M.